Knowledge of nursing students about human papillomavirus infection and vaccination - Andrade, Taciana Magna Feitosa de; Martins, Mariana Cavalcante; Gubert, Fabiane do Amaral; Freitas, Clarice Mendes de (Brazilian Journal of Sexually Transmitted Diseases, 2013)
Introduction: Sexually transmitted diseases (STDs) are one of the major health problems in the world. Among STDs, the Human Papillomavirus (HPV) infection is the most prevalent one, since approximately five hundred thousand to one million people are infected with this virus each year. Objective: To evaluate the knowledge of nursing students about the HPV and vaccination. Methods: A descriptive study with quantitative approach performed in a private higher education institution in Fortaleza, Ceará, Brazil. The sample consisted of students from the 1st and the 7th semester of nursing. Data were collected through a semi-structured questionnaire and analyzed with the SPSS, version 14.0, and descriptive statistics. Results: By characterizing the students, it was observed that 50.8% are older than 25 years old, 52.5% of them study and live only with help from their parents, and 80.3% reported having an active sex life. When questioning about what HPV is, there was a significant association (p = 0.008), whereas 42.6% of freshmen and 57.4% of 7th semester students reported what an STD is, 93.3% of students in the first semester and 71.0 % in the 7th semester were unaware of the vaccine. Conclusion: Most nursing students at the research institution have not enough knowledge about the virus, its consequences, and preventive forms of treatment, which may negatively influence the vulnerability of this age group.